Answer:
Step-by-step explanation:
3x - 4y = 13 (1)
2x + y = 5 (2)
——————
3x - 4y = 13
4(2x + y = 5) (2) times 4
——————-
3x - 4y = 13
8x + 4y = 20
——————-
11x = 33
x = 33/11
x = 3
Plug x = 3 in (2):
2(3) + y = 5
6 + y = 5
y = 5-6
y = -1
Thus, x = 3 and y = -1
Answer:
Question 2: 58.88
Question 7: 30,000
Question 8: 213.7
Question 12: p(p+6)
Question 16: 16
Question 19: 35
That the best I could do
Hope It help If not then sorry try to help tho
Answer:
the answer would be D
Step-by-step explanation:
first you add all your marbles up and that is you bottom half of the equation and then you put the amount of white marbles on top.